2011
DOI: 10.1007/s10995-011-0865-y
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant and Recently Pregnant Women’s Perceptions about Influenza A Pandemic (H1N1) 2009: Implications for Public Health and Provider Communication

Abstract: The objective of this study was to explore pregnant and recently pregnant women's perceptions of influenza vaccine and antivirals during the 2009 H1N1 pandemic. We conducted 18 focus groups with pregnant and recently pregnant women in three US cities in September 2009. Participants were segmented into groups by insurance status (no or public insurance vs. private insurance), vaccine attitudes (higher vs. lower likelihood of acceptance of any vaccines, not only influenza vaccines), and parity (first child vs. o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(108 citation statements)
references
References 13 publications
1
107
0
Order By: Relevance
“…47,50 The desire to protect the fetus/infant and oneself from disease was a strong predictor of immunization. 22,23,29,34,42,46,55,56 Most consistently, having the vaccine recommended AND offered by their healthcare provider [21][22][23]25,28,29,[31][32][33][34][37][38][39][40]42,45,46,50,[54][55][56][57][58][59][60] and trusting the recommendations 47 were identified most frequently as important in increasing vaccine uptake. For influenza vaccine, prior vaccination of oneself 25,28,34,45,46,53,60 or one's partner 59 in previous years was a strong predictor of acceptance of vaccination during pregnancy.…”
Section: Factors Related To Pregnant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…47,50 The desire to protect the fetus/infant and oneself from disease was a strong predictor of immunization. 22,23,29,34,42,46,55,56 Most consistently, having the vaccine recommended AND offered by their healthcare provider [21][22][23]25,28,29,[31][32][33][34][37][38][39][40]42,45,46,50,[54][55][56][57][58][59][60] and trusting the recommendations 47 were identified most frequently as important in increasing vaccine uptake. For influenza vaccine, prior vaccination of oneself 25,28,34,45,46,53,60 or one's partner 59 in previous years was a strong predictor of acceptance of vaccination during pregnancy.…”
Section: Factors Related To Pregnant Womenmentioning
confidence: 99%
“…22,25,32,34,35 Protect baby and self from disease. 22,23,29,34,42,46,55,56 Text messaging with general pregnancy health and vaccination information, and appointment reminders. 81,82 Lack of vaccine knowledge.…”
Section: Factors Related To Healthcare Providers Recommending Vaccinesmentioning
confidence: 99%
“…Misperceptions of vaccine safety are a common contributor to low immunisation rates [2][3][4][5][6]. 60…”
Section: Introduction 57mentioning
confidence: 99%
“…Similar to other pandemic research, our survey found that witnessing the pandemic had a definite impact on seasonal and pandemic influenza vaccine coverage. Lynch et al 27 describe the impact of appraised threat to a pregnant women's perceptions of their vulnerability to, and the severity of, H1N1 and their subsequent preventive behavior. In our study, women in the postpandemic group stated they were more likely to get the seasonal vaccine after witnessing the pandemic, citing both their own safety and safety of their family as reasons.…”
Section: Discussionmentioning
confidence: 99%